Are socioeconomic status and type of residence critical risk factors of under-five mortality in Pakistan? Evidence from nationally representative survey - Lubna Naz; Kamalesh Kumar Patel; Azer Dilanchiev (Elsevier, 2021)
Introduction: Pakistan had the highest mortality rate (75/1000) among under-five children in the South Asia, followed by Afghanistan (68/1000) in 2017. This paper examines whether socioeconomic status and type of residence are crucial risk factors of under-five mortality or not in Pakistan. Methods: The bivariate and Cox Proportional Hazards regression were applied on a sample of 19,190 under-five children extracted from the Pakistan Demographic and Health Survey 2017-18 to examine the impacts of risk factors on under-five mortality. Results: The rich families were associated with 28% reduced risks (HR = 0.72; 95% CI: 0.64-0.81) of under-five mortality compared to the poor, and urban had 19% a lower risk (HR = 0.81; 95% CI: O.73-0.89) compared to rural (model 1). Educated mothers had 25 lower risk mothers (HR = 0.75; 95% CI:0.60-0.93), mothers aged 18 years and above at first birth had 21% lower risk (HR = 0.79; 95% CI: 0.65-0.95); mothers experiencing birth spacing of more than 3 years were associated with 44% lower risk (HR = 0.56; 95% CI: 0.45-0.69); average birth size was associated with 36% lower risk (HR = 0.64; 95% CI: 0.51-0.78), and female child with 11% reduced risk (HR = 0.64; 95% CI: 0.51-0.78), whereas socioeconomic status and type of residence were not statistically significant (model 2). Conclusion: The results call for revisiting healthcare policies and propose holistic programs for under-five mortality reduction in Pakistan.